Teaching and learning strategies in the process of environmental conservation among students of school "Juan Velasco Alvarado" - Pillcomarca - Huánuco - Vasquez-Salis, Yermmy (2019)
This research is part of the learning strategies teaching in the process of environmental conservation, the problem was general how does teaching and learning strategies in preserving the environment in the students of school "Juan Velasco Alvarado" - Pillcomarca - Huánuco?, having as general objective: to determine the influence of teaching and learning strategies in preserving the environment in the students of school " Juan Velasco Alvarado "- Pillcomarca - Huánuco. The research was explanatory, quasi-experimental design, with pre and post test experimental group and control group, with a population consisting of 356 students. The sample consisted of 62 sixth graders of elementary level School "Juan Velasco Alvarado” of Pillcomarca - Huánuco, which was selected by convenience sampling and documentary art, coding and tabulation, which concluded that the strategies teaching and learning adequately influence the development of reactive behavioral factors for environmental conservation of students of school "Juan Velasco Alvarado" - Pillcomarca – Huánuco.